Trauma, genes, or spirits? Development of a scale to provide a more nuanced understanding of refugees' causal attributions for mental health problems - Lars Dumke; Sarah Wilker; Hawkar Ibrahim; Cara Hohaus; Frank Neuner (Elsevier, 2023)
Only a small proportion of refugees requiring treatment actually receive psychotherapy. Alongside structural barriers, it has been hypothesized that causal attributions for mental health problems that deviate from Western explanatory models may reduce refugees' help-seeking behavior. Prevailing assumptions suggest that refugees predominantly hold causal beliefs that are incompatible with the rationales of psychotherapy. Testing these assumptions requires a reliable assessment tool to evaluate refugees' causal beliefs. Therefore, we developed the Causal Attributions for Mental Health Problems Scale (MH-CAUSE) and validated it in a sample of Middle Eastern refugees living in Germany (N = 429). The outcomes of the psychometric analysis, which included exploratory and confirmatory factor analysis, internal consistency, and convergent validity, indicate that the MH-CAUSE is a suitable instrument for assessing refugees' causal beliefs about mental health problems. Our findings suggest that refugees' causal attributions are in line with a biopsychosocial-spiritual model of mental illness. Contrary to common assumptions, the majority of participants predominantly explained mental illness via psychosocial and biomedical causes, whereas spiritual beliefs were relevant only for a minority of participants. We observed significant associations between causal beliefs and help-seeking attitudes and behavior. However, effect sizes were only small to moderate. While mental health beliefs might contribute to mental health inequities, alleged cultural differences of refugees should not be overemphasized.